Substandard journal management: wastage of authors’ motivation - Sorooshian, Shahryar; Parsia, Yasaman (MDPI AG, 2018)
Authors who offer papers for publication to professional journals are under the impression that their work is publication-worthy. The editors as well as reviewers adjudge whether the manuscripts should be taken up for publication. This paper presents certain cases of unreliable journals’ management processes with an aim to show how a journal reviewer or editor could squander authors’ time and negatively impact the motivation of scholars to publish.